REINVESTIGATING THE GUIDANCE FOR JIHAD AGAINST COLONIALISM IN MALAY LANDS: A PHILOLOGICAL STUDY ON SHEIKH ABDUS SAMAD AL-PALIMBANI'S NASHIHAH AL-MUSLIMIN WA TADHKIRAH AL-MUKMININ - Mia Fitriah El Karimah (UIN Kiai Haji Achmad Siddiq Jember, 2023)
The wars of the colonial era in the Malay region, especially in Sumatra, could not be separated from the influence of the jihad campaign of Sheikh Abdus Samad al-Palimbani, a charismatic cleric at that time. This research examines al-Palimbani’s Nashihah al-Muslimin wa Tadhkirah al-Mukminin, which contains the call for jihad. Because this manuscript is hundreds of years old and this condition makes it difficult to read, this research uses philological studies using a single script and standard script methods. It means that the manuscript being examined is the only one, and there are no copies. Research shows that the text is a European manuscript type even though it uses Arabic and the cover is identical to the typical style of the Arabian Peninsula. Apart from that, this manuscript also provides information about jihad by containing quotations from verses from the Qur’an and hadiths of the Prophet Muhammad. However, jihad here is understood to be limited to struggle on the physical war. Therefore, the manuscript encloses several dhikrs and prayers during the war. Furthermore, this manuscript was motivated by the colonial occupation of Malay land.